Degradation of Natural Undaria pinnatifida into Unsaturated Guluronic Acid Oligosaccharides by a Single Alginate Lyase - Hui Wang; Jiaqi Wen; Nuraliya Ablimit; Kun Deng; Wenzhuo Wang; Wei Jiang (Marine Drugs)
Here, we report on a bifunctional alginate lyase (Vnalg7) expressed in Pichia pastoris, which can degrade natural Undaria pinnatifida into unsaturated guluronic acid di- and trisaccharide without pretreatment. The enzyme activity of Vnalg7 (3620.00 U/mL-culture) was 15.81-fold higher than that of the original alg (228.90 U/mL-culture), following engineering modification. The degradation rate reached 52.75%, and reducing sugar reached 30.30 mg/mL after combining Vnalg7 (200.00 U/mL-culture) and 14% (w/v) U. pinnatifida for 6 h. Analysis of the action mode indicated that Vnalg7 could degrade many substrates to produce a variety of unsaturated alginate oligosaccharides (AOSs), and the minimal substrate was tetrasaccharide. Site-directed mutagenesis showed that Glu238, Glu241, Glu312, Arg236, His307, Lys414, and Tyr418 are essential catalytic sites, while Glu334, Glu344, and Asp311 play auxiliary roles. Mechanism analysis revealed the enzymatic degradation pattern of Vnalg7, which mainly recognizes and attacks the third glycosidic linkage from the reducing end of oligosaccharide substrate. Our findings provide a novel alginate lyase tool and a sustainable and commercial production strategy for value-added biomolecules using seaweeds.